Implications of Crude Oil Price Volatility and Parallel Exchange Rate Fluctuation on the Cost of Living in Nigeria - Okolo, Chimaobi V (Journal of Challenges, 2017)
As the sixth largest exporter of crude oil, Nigeria heavily depends on oil earnings to fund economic activities. The country also rely heavily on imports of consumables, both oil and non oil consumables. Nigeria’s vulnerability to crude oil price shock at the international oil market exposes the nation to certain unfavourable results. The study investigated the influence of crude oil price volatility on parallel exchange rate and their influence on the cost of living and doing business in Nigeria. Two stage least square, generalized autoregressive conditional heteroscedasticity, vector error correction, impulse response and variance decomposition was employed to measure the influence of crude oil price on parallel exchange rate and their influence on cost of living in Nigeria. Crude oil price volatility negatively and significantly influenced parallel exchange rate fluctuation and consumer price index in Nigeria. Parallel exchange rate positively and significantly influenced consumer price index in Nigeria. Declining crude oil prices implies decreasing income for the Nigerian economy and in turn per capita income. Rising cost of living with declining per capita income further impoverishes Nigerians. Therefore Nigeria should effectively take control of the production of crude oil, increase her refining capacity and increase production and export of other products with comparative advantages.